Answer:
Step-by-step explanation:
As stated in the question, the probability to toss a coin and turn up heads in the first try is [tex]\frac{1}{2}[/tex], in the second is [tex]\frac{1}{4}[/tex], in the third is [tex]\frac{1}{8}[/tex] and so on. Then, P(C) is given by the next sum:
[tex]P(C)=\sum^{\infty}_{n=1}(\frac{1}{2} )^{n}=1[/tex]
This is a geometric series with factor [tex]\frac{1}{2}[/tex]. Then is convergent to [tex]\frac{1}{1-\frac{1}{2}}-1=1.[/tex]. With this we have proved that P(C)=1.
Now, observe that
[tex]P(H)=\frac{1}{2}, P(TH)=\frac{1}{4},P(TTH)=\frac{1}{8},P(TTTH)=\frac{1}{16},P(TTTTH)=\frac{1}{32},P(TTTTTH)=\frac{1}{64}.[/tex]
Then
[tex]P(C1)=P(H)+P(TH)+P(TTH)+P(TTTH)+P(TTTTH)=\frac{1}{2} +\frac{1}{4} +\frac{1}{8} +\frac{1}{16} +\frac{1}{32} =\frac{31}{32}[/tex]
[tex]P(C2)=P(TTTTH)+P(TTTTTH)=\frac{1}{32}+\frac{1}{64} =\frac{3}{64}[/tex]
[tex]P(C1\cap C2)=P(TTTTH)=\frac{1}{32}[/tex]
and
[tex]P(C1\cup C2)=P(H)+P(TH)+P(TTH)+P(TTTH)+P(TTTTH)+P(TTTTTH)=\frac{1}{2} +\frac{1}{4} +\frac{1}{8} +\frac{1}{16} +\frac{1}{32} +\frac{1}{64}=\frac{63}{64}[/tex]